Why can’t main project management functions be achieved in most construction projects? - Moura, Helder M. Pinto (2006)
The lack of accomplishment of the main management functions in construction projects had been reported worlwide. The symptoms are well recognized, like cost and time overruns, deficient quality and lack of safety. To help clarifying the reasons for this evidence, a survey was carried to Portuguese construction stakeholders, based on an Internet inquiry, aimed to characterize past projects. While time for the answers is still running, the main important conclusion retrieved from the survey is that industry practicioners do not have, or do not want to provide, quantitative information about past projects. This, in fact, may be signalled as the first reason for the lack of competitiveness of the construction industry in Portugal.